2021
DOI: 10.3390/ijerph18084344
|View full text |Cite
|
Sign up to set email alerts
|

Is a Mask That Covers the Mouth and Nose Free from Undesirable Side Effects in Everyday Use and Free of Potential Hazards?

Abstract: Many countries introduced the requirement to wear masks in public spaces for containing SARS-CoV-2 making it commonplace in 2020. Up until now, there has been no comprehensive investigation as to the adverse health effects masks can cause. The aim was to find, test, evaluate and compile scientifically proven related side effects of wearing masks. For a quantitative evaluation, 44 mostly experimental studies were referenced, and for a substantive evaluation, 65 publications were found. The literature revealed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
194
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(206 citation statements)
references
References 144 publications
(764 reference statements)
8
194
0
4
Order By: Relevance
“…Habitual loud speech is well known to increase the risk of phonotrauma; however, such risk has not yet been completely understood with regard to facemask use during the pandemic. From a recent systematic review on effects of facemask use on different dimensions, effects on perceived vocal health are described to be assessed in only one study 18 . This was an investigation on the prevalence of self-perceived voice handicap during COVID19 outbreak in Chile, measured by means of the short version of the Voice Handicap Index (VHI-10).…”
Section: Introductionmentioning
confidence: 99%
“…Habitual loud speech is well known to increase the risk of phonotrauma; however, such risk has not yet been completely understood with regard to facemask use during the pandemic. From a recent systematic review on effects of facemask use on different dimensions, effects on perceived vocal health are described to be assessed in only one study 18 . This was an investigation on the prevalence of self-perceived voice handicap during COVID19 outbreak in Chile, measured by means of the short version of the Voice Handicap Index (VHI-10).…”
Section: Introductionmentioning
confidence: 99%
“…Potential health-related side-effects of wearing face masks are discussed. Recent systematic reviews addressed potential side effects and discomforts concerning the use of community masks, medical/surgical masks and FFP2/N95-masks with regard to a risk-benefit analysis [4,5]. Kisielinski et al [5] found a significant effect of face masks, especially N95-masks, on the blood-oxygen depletion and symptoms of fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews addressed potential side effects and discomforts concerning the use of community masks, medical/surgical masks and FFP2/N95-masks with regard to a risk-benefit analysis [4,5]. Kisielinski et al [5] found a significant effect of face masks, especially N95-masks, on the blood-oxygen depletion and symptoms of fatigue. The use of masks was also associated with headache, exertion, concentration problems and breathing difficulties [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations